Crystal structure of 2-[(4-bromobenzyl)thio]-5-(5-bromothiophen-2-yl)-1,3,4-oxadiazole, C13H8Br2N2OS2 - Al-Omary, Fatmah A. M.; Blacque, Olivier; Alanazi, Fahdah S.; Tiekink, Edward R. T. *; El-Emam, Ali A. (De Gruyter Open, 2023)
C13H8Br2N2OS2, monoclinic, Pc (no. 7), a = 13.4050(4) Å, b = 4.7716(1) Å, c = 11.7303(4) Å, β = 105.885(3)∘, V = 721.66(4) Å3, Z = 2, Rgt(F) = 0.0294, wRref(F2 = 0.0808, T = 160 K.